Research on the influence of consumer Perceived Value on the purchase of new energy vehicles - Hu, Xiaofang; Raja Yusof, Raja Nerina; Dato Mansor, Zuraina (Editorial Salud, Ciencia y Tecnologia, 2024)
In recent years, low carbon economy has gradually become a hot issue of global concern. At present, Chinese consumers are still in the initial stages of understanding and research on carbon tax. By analysing various carbon tax regimes domestically and abroad, this article employs a quantitative research methodology to explore the influence of consumer perceptions on customers’ purchase of new energy vehicles. This paper concentrates on the operational models of several major carbon tax systems at home and abroad and provides a thorough overview of the setting of carbon tax schemes, risk management, and the economics of carbon trading in each country. Drawing on the experiences of foreign countries and regions in implementing carbon tax schemes, this paper offers suggestions on how China can design carbon tax policies to promote green consumption behavior among contemporary Chinese consumers. © 2024; Los autores.